Anisotropic conductive reduced graphene oxide/silk matrices promote post-infarction myocardial function by restoring electrical integrity. (February 2022) - Zhao, Guoxu; Feng, Yanjing; Xue, Li; Cui, Mengjie; Zhang, Qi; Xu, Feng; Peng, Niancai; Jiang, Zhuangde; Gao, Dengfeng; Zhang, Xiaohui
Abstract: Myocardial infarction (MI) remains the leading cause of death globally, often leading to impaired cardiac function and pathological myocardial microenvironment. Electrical conduction abnormalities of the infarcted myocardium not only induce adverse myocardial remodeling but also prevent tissue repair. Restoring the myocardial electrical integrity, particularly the anisotropic electrical signal propagation within the injured area after infarction is crucial for an effective function recovery. Herein, optimized reduced graphene oxide (rGO) functionalized electrospun silk fibroin (rGO/silk) biomaterials presenting anisotropic conductivity and enhanced suturablity were developed and investigated as cardiac patches for their potential in improving the post-MI myocardial function of rat models. The results show that the anisotropic conductive rGO/silk patches exhibit remarkable therapeutic effect on repairing the infarcted myocardium compared to the nonconductive silk and isotropic conductive rGO/silk patches as determined by the enhanced pumping function, reduced susceptibility to arrhythmias, thickened left ventricular walls and improved survival of functional cardiomyocytes. Their notable effect on promoting the angiogenesis of capillaries in the infarcted myocardium has also been demonstrated. This study highlights an effective and biomimetic reconstruction of the electrical myocardial microenvironment based on the anisotropic conductive rGO/silk biomaterials as a promising option for promoting the repair of infarcted myocardium. Statement of significance: The dysfunctional electrical microenvironment in the infarcted myocardium not only aggravates the adverse myocardial remodeling but also limits the effect of cardiac regenerative medicine. Although various conductive biomaterials have been employed to restore the electrical network in the infarcted myocardium in vivo, the anisotropic nature of the myocardial electrical microenvironment which enables directional electrical signal propagation were neglected. In this study, an anisotropic conductive rGO/silk biomaterial system is developed to improve the myocardial function post infarction by restoring the anisotropic electrical microenvironment in the infarcted myocardium. The promoted effects of anisotropic conductive grafts on repairing infarcted hearts are demonstrated with improved pumping function, cardiomyocyte survival, resistance to ventricular fibrillation, and angiogenesis of capillary network. Graphical abstract: Image, graphical abstract